PENGARUH PELAKSANAAN PEMBERDAYAAN MASYARAKAT MELALUI PROGRAM PENGEMBANGAN LEMBAGA EKONOMI PEDESAAN TERHADAP PENINGKATAN KESEJAHTERAAN MASYARAKAT DI KECAMATAN RUMBAI KOTA PEKANBARU PROPINSI RIAU - Fabillah Sandi (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2008)
The research aims at studying the local efforts in improving community welfare and alleviating poverty in Pekanbaru City. One among other programs in alleviating poverty in Pekanbaru City is by providing grants to the village communities so that they are encouraged to actively participate in the development process. The grant is called Village Saving and Credit Services (UED-SP) for micro, small, and medium enterprises at the village level. The services should consider the localnatural potentials and needs. The objective of the program is to improve local economic development. The Village Economic Institutional Development program as a means to empowering people should put local people as the subject as well as the object all along the stages of development process.